Hubungan Perawatan Wajah Dengan Akne Vulgaris - Siti Khomsatin; Shally Ayu Chintya; Euis Syafaiqoh (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Acne vulgaris is a commonsinflammatory condition of the skin organscalled the polysebaceous unit that occurs in adolescents and youngeadults characterized by comedones, papules, pustules andsnodules. This study aims to examinesthe relationshipsbetween facial care and acne vulgaris in female adolescents of PP Darussalam Putri Utara. This research is a quantitativerresearch with a descriptivesapproach. The sample selection used a random sampling technique, namely five young women of PP Darussalam Putri Utara with cases of acne vulgaris. Vulnerable age 20-23 years. Samples (respondents) were given product X for facial treatment for 30 days. Data collection was carried out on the 7th day, 14th day, 20th day and 30th day. Basedson the results of the study, it can1be concluded that (1) good and correct facial care, with products that are suitable for skin conditions and types, can reduce the problem of acne vulgaris in adolescent girls in PP Darussalam Putri Utara. (2) there is a correlation between facial care and acne vulgaris, facial treatment is negatively related to acne vulgaris with a moderate degree of correlation or it can be interpreted that the better facial treatments are carried out, the more acne vulgaris is reduced in female students of PP Darussalam Putri North